مسح التطورات الاقتصادية والاجتماعية 2020-2019 - United Nations Economic; Social Commission for Western Asia (United Nations, 2021)
This annual flagship publication seeks to both analyze routinely monitored economic and social variables in the Arab region in a global context as well as address debt sustainability and the macroeconomic implications. Given that the COVID-19 pandemic will have significant repercussions in 2021 and beyond, it is crucial to understand how Arab countries are dealing with the economic impact of the virus. The report sets out two scenarios: a baseline scenario projecting that the economy will rebound in the first quarter of 2021; and a pessimistic scenario in which the crisis will persist throughout the first quarter of 2021. However, given considerable advancements in research on COVID-19 vaccines, an economic rebound should be expected no later than the second quarter of 2021.